2016
DOI: 10.1177/0956797616671524
|View full text |Cite
|
Sign up to set email alerts
|

The Whole Warps the Sum of Its Parts

Abstract: The efficiency of averaging properties of sets without encoding redundant details is analogous to gestalt proposals that perception is parsimoniously organized as a function of recurrent order in the world. This similarity suggests that grouping and averaging are part of a broader set of strategies allowing the visual system to circumvent capacity limitations. To examine how gestalt grouping affects the manner in which information is averaged and remembered, I compared the error in observers' adjustments of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…Unbiased reporting of each pleasure and the average of both when viewing two images People are biased toward the average of an array when reporting properties (e.g., size or color) of a single item (Brady & Alvarez, 2011;Corbett, 2017;Haberman & Whitney, 2009;Maule et al, 2014;Parkes et al, 2001). So far, it has not been assessed whether people have a similar bias when reporting their subjective feelings about a stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unbiased reporting of each pleasure and the average of both when viewing two images People are biased toward the average of an array when reporting properties (e.g., size or color) of a single item (Brady & Alvarez, 2011;Corbett, 2017;Haberman & Whitney, 2009;Maule et al, 2014;Parkes et al, 2001). So far, it has not been assessed whether people have a similar bias when reporting their subjective feelings about a stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings could not be explained by supposing that observers simply make noisy measurements of each individual face's emotion. When estimating the size of a single dot, observers' estimates are biased toward the average size of all presented dots (Brady & Alvarez, 2011;Corbett, 2017). People are also biased to mistake the average color of two simultaneously presented color patches as being one of the originally presented colors (Maule et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, the visual system relies on a default set of heuristic regularities in the external environment to guide the formation of initial perceptual chunks, which pragmatically constrain further processing (e.g., Wertheimer, 1938 ). These perceptual chunks likely consist of sparse statistical representations of redundant information (Corbett, 2017 ). Toward furthering our understanding of how the limited-capacity visual system relies on such higher order regularities to organize and segregate information in dynamic environments, we examined how observers utilized grouping by similarity to track a target within a display composed of one or more subsets of objects.…”
mentioning
confidence: 99%
“…Similarly, Brady and Tenenbaum ( 2013 ) reported that grouping by similarity and proximity improved change-detection performance compared with performance with arrays that did not contain Gestalt grouping cues. More recently, Corbett ( 2017 ) reported that when observers viewed study displays of heterogeneously sized circles organized into two different Gestalt-defined mean size groups, followed by test displays of a subset of homogeneously sized circles and were asked to adjust the test circles to the remembered sizes of the corresponding circles in the study displays, they made more similar (correlated) errors for test circles in the same Gestalt-defined groups. Their adjustments of physically identical test circles were also biased toward the mean sizes of the corresponding Gestalt-defined group mean sizes.…”
mentioning
confidence: 99%
See 1 more Smart Citation